2010
DOI: 10.1007/s10815-010-9450-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-survival, fertilization and early embryonic development of vitrified oocytes derived from mice of different reproductive age

Abstract: Purpose To evaluate the effect of female reproductive age on oocyte cryo-survival, fertilization and the subsequent embryonic development following vitrification using the mouse model in order to address the question of how maternal reproductive age is related to fertility preservation. Methods Oocytes were collected from mice of different reproductive age: (1) 8-10 weeks, (2) 16-20 weeks, (3) 32-36 weeks, and (4) 44-48 weeks. Following vitrification and warming, the oocytes in each group were assessed for cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In addition, low total cell number of the blastocysts was also observed in mice [53]. When OGCs of EAFs were cultured in medium containing 0.1 μg/mL E 2 , the ratio of polyspermic fertilization of oocytes grown in vitro was higher for aged groups than that for young groups.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, low total cell number of the blastocysts was also observed in mice [53]. When OGCs of EAFs were cultured in medium containing 0.1 μg/mL E 2 , the ratio of polyspermic fertilization of oocytes grown in vitro was higher for aged groups than that for young groups.…”
Section: Discussionmentioning
confidence: 97%
“…In addition many of the studies that demonstrate comparable pregnancy rates between fresh and vitrified oocytes are undertaken using young oocyte donors and it is likely that oocyte quality can play a role susceptibility to damage during cryopreservation [14]. Studies using animal models have demonstrated that the negative impact of vitrification on the oocyte increases with maternal age so it is likely that the impact of vitrification in older women will be far greater than that of young donors however this has not been investigated [71].…”
Section: Discussionmentioning
confidence: 99%
“…However, in cows, non-surgical frozen ET resulted in lower pregnancy rate compared with surgical transfer (38.5 vs 71.1%). In a study on mouse oocytes, age-related decrease in the number of oocytes retrieved following superovulation was noted (Yan et al 2010). Oocytes retrieved from older females had lower survival and cleavage rate after vitrification, rate of development to blastocyst went down with maternal age when oocytes were vitrified but not in the control (no vitrification), and blastocyst quality (total cell number and ratio of inner cell mass to trophectoderm) was lower in the older age groups in both vitrified and control treatments.…”
Section: Agementioning
confidence: 99%